Value and Character Education in the Perspective of General Education in Higher Education - Fuadaturrahmah Fuadaturrahmah; Sukma Ningtias; Doni Setiari; Ebenezer Tarigan; Desnor Steven Waruwu; Waruwu Waruwu; Delfin Masna Gulo; Dwi Agillia Putri; Dhea Reni Anggraini (Pusdikra-Publishing.com, 2024)
To effectively address the growing complexity of living conditions, its crucial to use a comprehensive and multidisciplinary approach. Engaging with experts from many scientific fields s crucial for finding tailored answers to complex problems that require knowledge from multiple disciplines. Library research s utilised to investigate and clarify data. This inquiry utilises literature the form of rules to assess the value and character education higher education from a general education perspective. The aim of this study s to examine and offer arguments concerning the subjects of value and character education higher education institutions Indonesia, focusing on the perspective of general education. Here s a brief overview of the findings from this investigation: General education, sometimes known as